MENYONGSONG REFORMASI BIROKRASI TAHAP KEDUA MELALUI PENINGKATAN KUALITAS PELAYANAN PUBLIK - ana, Meili (Jurnal Borneo Administrator, 2011)
Improved governance at this time is encouraged through the implementation of bureaucratic reforms program that has entered the second stage (2010-2014). One considerable area of change in the bureaucratic reform that needs to be improved is public services, especially in the current era of regional autonomy nowadays where the regions have opportunity to innovate, be creative, and create the best model to achieve improved quality of service to the community. One important effort suggested by the author to improve the quality of public services is to do public service management reform, to fulfill completeness of organizational development, and implementation of zero management in public service activities. If this can be implemented, it is expected that people's satisfaction is achieved, which together will show the better performance of the government, and in the aggregate will show the successful implementation of bureaucratic reforms.Keywords : Bureaucratic reform, public service, regional autonomyPerbaikan tata kelola pemerintahan yang saat ini digalakkan melalui pelaksanaan program reformasi birokrasi sudah memasuki tahapan atau gelombang kedua (2010-2014). Salah satu area perubahan reformasi birokrasi yang cukup penting untuk ditingkatkan adalah pelayanan publik, terutama di era otonomi daerah saat ini yang memberikan kesempatan kepada daerah untuk berinovasi, berkreasi, dan menciptakan model terbaik demi pencapaian peningkatan kualitas pelayanan kepada masyarakat. Upaya penting yang disarankan oleh penulis untuk meningkatkan kualitas pelayanan publik adalah dengan melakukan pembenahan manajemen pelayanan publik, memenuhi kelengkapan pengembangan organisasi, serta penerapan manajemen zero dalam aktivitas pelayanan publik. Jika hal ini mampu dilaksanakan, maka diharapkan kepuasan masyarakat akan tercapai, yang secara bersinergi menunjukkan kinerja pemerintahan yang semakin baik, dan secara agregat menunjukkan keberhasilan pelaksanaan reformasi birokrasi. Kata Kunci : Reformasi Birokrasi, Pelayanan Publik, Otonomi Daerah